Kebebasan media komunikasi menurut perspektif Islam - Aminudin Basir @ Ahmad,; Mohamad Sabri Haron,; Nik Yusri Musa, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
Media and communication are inseparable from the message. To ensure that the message is truthful and reliable, freedom (of expression) is necessary. Without freedom in message delivery it will be an uphill task for media communication to obtain its goals. To safeguard the public and national security, the freedom of the media in obtaining the message and disseminating it must operate within an environment regulated by law and strong moral codes. Therefore, Islamic teachings must form the basis on which guidelines, conducts and ethics of communication and the nation’s media are based. Consumers of media communication on the other hand should be selective in giving beneficial messages based on proper conducts. There needs to be a strict enforcement to ensure that media communication is able to serve its function as an agent for educating society. Universities should lay out a syllabus for media communication that is more cultured and morally responsible. In addition, it is imperative that syariah panels acting as advisors to media communication bodies be set up. Document analysis revealed that acts related to the country’s freedom of media communication are already in place. Analysis also showed that Islamic jurisprudence formulated principles that need to be taken into account in the practice of freedom of media communication. In view of this, this article discusses the freedom of media communication from the Islamic perspective.